Synthesis, characterization and application of polypyrrole graphene oxide nanocomposite as sorbent in green microextraction of tetracycline antibiotics in aqueous matrices / Nurzaimah Zaini @ Othman - Zaini @ Othman, Nurzaimah (2024)
The widespread use and improper disposal of tetracycline antibiotics has led to their contamination in water sources, posing a significant threat to public health, necessitating the urgent development of sensitive and reliable analytical methods for detecting antibiotics at low concentrations to ensure public safety and preventing the emergence of antibiotic-resistant diseases. Sample preparation for pharmaceutical contaminant analysis poses significant challenges due to the multi-step and timeconsuming procedures of conventional methods. Hence, motivated by the arising issues, this research is conducted to explore the application of the synthesized polypyrrole-graphene oxide (PPy-GO) for dispersive micro solid phase extraction (Dµ-SPE) sorbent and its manual packing into the online solid-phase extraction liquid chromatography (online SPE-LC) column, introducing a novel and green approach for tetracycline antibiotic analysis in water samples through efficient processes that reduce solvent usage. Selected commonly used TCs namely oxytetracycline (OTC), tetracycline (TC), demeclocycline (DMC), chlortetracycline (CTC), and doxycycline (DC) were used as target analytes. PPy-GO composite sorbent was synthesized and characterized by Fourier Transform Infrared (FTIR) spectroscopy, Field Emission Electron Microscope (FESEM), thermogravimetric analysis (TGA), X-ray diffraction (XRD) and Brunauer-Emmet-Teller (BET) analyzer. Several parameters were optimized in D-μ-SPE method.